Modified silica ash porous lightweight concrete-based thermal insulation material and preparation method thereof

CN118580093BActive Publication Date: 2026-10-20ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410621576.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2026-10-20
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

但其生产成本高,同时还由于细小颗粒易被人体吸入而提高了生产过程中的潜在风险

Benefits of technology

[0026]1.本发明提出了料浆初始流动度/屈服应力的最佳范围,在此最佳范围和发气环境下,料浆的发气过程与稠化过程能良好匹配,生成的气泡能自由膨胀而不过渡溢出。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580093B_ABST
    Figure CN118580093B_ABST
Patent Text Reader

Abstract

The application discloses a modified silica ash porous lightweight concrete-based thermal insulation material and a preparation method thereof, and belongs to the technical field of thermal insulation materials. The material is composed of the following components in 100 mass parts of slurry: cement 25.0-27.2 parts, superfine filler 36.0-37.1 parts, modified silica ash 0.9-3.1 parts, lime 0.6-1.6 parts, early strength agent 0.7-1.2 parts, foam stabilizer 0.2-0.4 parts, gas-forming agent 0.2-0.4 parts, water reducing agent 0.4-0.9 parts and water 31.3-32.6 parts. The silica ash of a specific particle size is modified and treated, and its contact angle is controlled in an optimal range. The modified silica ash can be stably adsorbed to the gas-liquid interface, thereby greatly improving the foam stability of the slurry, and the pore structure and thermal insulation performance of the porous lightweight concrete-based thermal insulation material are optimized. The modified silica ash porous lightweight concrete-based thermal insulation material has the advantages of light weight, excellent thermal insulation and sound insulation effects, good strength performance and low cost, and is suitable for various thermal insulation scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermal insulation materials technology, and in particular relates to a modified silica fume porous lightweight concrete-based thermal insulation material and its preparation method. Background Technology

[0002] Porous concrete plays a crucial role in concrete products, its internal pore structure contributing to its rich physical properties. Firstly, the pore structure significantly reduces the density of concrete, making it lighter than traditional concrete. This gives porous concrete advantages in reducing structural weight, lowering foundation load, and improving construction efficiency. Simultaneously, the pore structure effectively reduces heat conduction, providing superior thermal insulation and fire resistance. This helps reduce building energy consumption and improve the safety of high-rise buildings, enhancing energy efficiency. Furthermore, the pore structure within porous concrete possesses sound absorption and insulation properties, reducing noise propagation and echoes, and providing a better indoor acoustic environment.

[0003] Based on the formation mechanism of pores in concrete, porous concrete can be divided into two main categories: physically foamed porous concrete and chemically foamed porous concrete. The essential difference between physical and chemical foaming lies in whether a chemical reaction is involved in the foam formation process. However, both methods involve uniformly mixing a foam system into the concrete slurry until the slurry completely solidifies, at which point the foam system transforms into the pore structure within the porous concrete product. However, precisely before the slurry solidifies, the foam system in the concrete slurry continuously grows and merges under the influence of three instability mechanisms: liquid film drainage, bubble disproportionation, and bubble coalescence. This increases the average pore size and open porosity of the final pore structure, deteriorating the material's thermal insulation effect and other comprehensive properties. Therefore, taking measures to suppress foam instability is of great significance for optimizing the pore structure and comprehensive properties of porous concrete.

[0004] Solid-phase particle stabilization has proven to be an effective method for stabilizing foam. Under certain particle size and contact angle conditions, these particles can automatically adsorb to the gas-liquid interface, thereby greatly enhancing the strength and anti-interference ability of the liquid film, while increasing the resistance to liquid film drainage, gas diffusion, and bubble coalescence, and significantly improving the foam stabilization effect. To increase the number of particles adsorbed per unit liquid film area, the solid-phase particles currently used are mostly nanoscale, such as nano-silicon, with individual particle sizes of several nanometers and an optimal contact angle of about 90°. However, their production cost is high, and the potential risks during production are increased because the small particles are easily inhaled by the human body. For solid-phase particles with larger particle sizes, although their cost advantage is obvious and the safety risk is lower, they face problems such as reduced adsorption quantity and particle desorption due to increased gravity, thus weakening the foam stabilization effect of the particles. Therefore, how to modify larger particle sizes to maintain their high adsorption quantity and stable adsorption capacity is of great significance for optimizing the pore structure of porous concrete and reducing its preparation cost. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a modified silica fume porous lightweight concrete-based thermal insulation material and its preparation method.

[0006] The specific technical solution adopted in this invention is as follows:

[0007] In a first aspect, the present invention provides a modified silica fume porous lightweight concrete-based thermal insulation material. The slurry composition of the modified silica fume porous lightweight concrete-based thermal insulation material per 100 parts by weight includes: 25.0–27.2 parts cement, 36.0–37.1 parts ultrafine filler, 0.9–3.1 parts modified silica fume, 0.6–1.6 parts lime, 0.7–1.2 parts early-strength agent, 0.2–0.4 parts foam stabilizer, 0.2–0.4 parts gas-generating agent, 0.4–0.9 parts water-reducing agent, and 31.3–32.6 parts water.

[0008] The modified silica fume has a particle size of 0.01–12 μm, an average particle size of not less than 0.1 μm, and a contact angle of 65–83°.

[0009] Preferably, the cement is silicate cement or early-strength sulfoaluminate cement, and the ultrafine filler is fly ash or metakaolin.

[0010] Preferably, the early strength agent is a calcium chloride type early strength agent or a sodium sulfate type early strength agent, the foam stabilizer is a calcium stearate type foam stabilizer, the gas generating agent is a surfactant, hydrogen peroxide or aluminum powder paste, and the water reducing agent is a polycarboxylate type water reducing agent.

[0011] Preferably, the preparation method of the modified silica fume is as follows:

[0012] S11: Weigh 10-30g of silica fume and dry it at 105℃ for 8-15 hours to obtain dried silica fume;

[0013] S12: Mix anhydrous ethanol and water in a volume ratio of 1:1 to 1:3 to obtain 300 to 600 mL of ethanol mixture; add oxalic acid aqueous solution with a concentration of 1 to 3 g / L dropwise to the ethanol mixture until the pH of the solution is 4.0 to 4.7; then add 0.5 to 2 g of KH570 silane coupling agent to obtain KH570 aqueous solution; place the KH570 aqueous solution in an environment of 20 to 26 °C for hydrolysis for 0.5 to 1 hour;

[0014] S13: Add the dried silica fume to the hydrolyzed KH570 aqueous solution and ultrasonically disperse for 5-10 minutes to obtain a silica fume dispersion;

[0015] S14: Stir the silica fume dispersion at 60-70°C for 0.5-1.5 hours;

[0016] S15: Centrifuge the silica fume dispersion obtained in S14 and repeatedly wash away the residual KH570 in the solution with an ethanol aqueous solution to obtain silica fume filter material;

[0017] S16: Dry the silica fume filter material at 60-80°C for 10-12 hours to obtain modified silica fume.

[0018] Preferably, the initial fluidity of the slurry is 125–138 mm, and the initial yield stress is 22.0–32.5 Pa.

[0019] Secondly, the present invention provides a method for preparing the modified silica fume porous lightweight concrete-based thermal insulation material according to any one of the first aspects, as follows:

[0020] S21: Cement, ultrafine filler, modified silica fume, lime, early strength agent and foam stabilizer are stirred at 600-900 rpm for 0.5-1 minute to obtain the first mixture; water-reducing agent is uniformly mixed with some water to obtain water-reducing agent solution; the remaining water is uniformly mixed with gas-generating agent to obtain gas-generating agent solution.

[0021] S22: Add the water-reducing agent solution to the first mixture and stir at 2000-2300 rpm for 3-5 minutes, then add the gas-generating agent solution and continue stirring for 0.5-1 minute to obtain a slurry;

[0022] S23: Pour the slurry into the mold, shake it evenly, and then place it under static conditions of 24-29℃ and 60%-90%RH for 1-2 days to allow gas to be generated.

[0023] S24: Demold after the gas generation is complete, and continue to cure at 24-29℃ and 60%-90%RH for 3-7 days;

[0024] S25: After curing, dry at 100-110℃ to constant weight, and after cooling, obtain the modified silica fume porous lightweight concrete-based thermal insulation material.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] 1. This invention proposes an optimal range for the initial fluidity / yield stress of the slurry. Within this optimal range and under the gas-generating environment, the gas-generating process of the slurry can be well matched with the thickening process, and the generated bubbles can expand freely without excessive overflow.

[0027] 2. This invention uses KH570 silane coupling agent to modify silica fume. The modified silane coupling agent has the advantages of excellent coupling performance, improved mechanical properties and durability of materials, wide applicability and environmental friendliness.

[0028] 3. This invention selects silica fume as the foam stabilizing particle, which has the advantages of moderate particle size, easy modification, low cost and high activity.

[0029] 4. This invention proposes the optimal particle size and corresponding optimal contact angle range for modified silica fume. Within this particle size and contact angle range, the modified silica fume can be stably adsorbed to the gas-liquid interface, exhibiting excellent foam stabilization effect.

[0030] 5. The silica fume modified porous concrete products proposed in this invention have the advantages of being lightweight, having excellent thermal insulation and sound insulation effects, good strength performance, and low cost, and are suitable for a variety of thermal insulation scenarios. Attached Figure Description

[0031] Figure 1 This is a flowchart of the preparation process for modified silica fume.

[0032] Figure 2 Flowchart for the preparation of modified silica fume porous lightweight concrete-based thermal insulation material.

[0033] Figure 3 The images show the FTIR results before and after silica fume modification.

[0034] Figure 4 These are TEM images showing the results before and after silica fume modification.

[0035] Figure 5 The images show the foam stabilization effect before and after silica fume modification.

[0036] Figure 6 These are photographs of the pore structures of ordinary porous concrete and modified silica fume porous lightweight concrete-based thermal insulation materials.

[0037] In the diagram, SF stands for silica fume; MSF stands for modified silica fume. Detailed Implementation

[0038] The present invention will be further described and illustrated below with reference to the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly, provided that there is no mutual conflict.

[0039] This invention provides a modified silica fume porous lightweight concrete-based thermal insulation material. This material is based on porous concrete, reinforced with modified silica fume, resulting in improved pore structure, enhanced thermal insulation performance, and increased strength. The slurry composition of every 100 parts by weight of this modified silica fume porous lightweight concrete-based thermal insulation material includes: 25.0–27.2 parts cement, 36.0–37.1 parts ultrafine filler, 0.9–3.1 parts modified silica fume, 0.6–1.6 parts lime, 0.7–1.2 parts early-strength agent, 0.2–0.4 parts foam stabilizer, 0.2–0.4 parts gas-generating agent, 0.4–0.9 parts water-reducing agent, and 31.3–32.6 parts water.

[0040] The modified silica fume has a particle size of 0.01–12 μm, an average particle size of not less than 0.1 μm, and a contact angle of 65–83°.

[0041] In a preferred embodiment of the present invention, the cement is ordinary silicate cement or early-strength sulfoaluminate cement, and the ultrafine filler is fly ash or metakaolin or other micron-sized fillers.

[0042] In a preferred embodiment of the present invention, the early strength agent is a calcium chloride type early strength agent or a sodium sulfate type early strength agent, the foam stabilizer is a calcium stearate type foam stabilizer, the gas generating agent is a surfactant, hydrogen peroxide or aluminum powder paste, and the water reducing agent is a polycarboxylate type water reducing agent.

[0043] As a preferred embodiment of the present invention, such as Figure 1 As shown, the specific method for preparing modified silica fume is as follows:

[0044] S11: Weigh 10-30g of ordinary silica fume and dry it at 105℃ for 8-15 hours to obtain dried silica fume.

[0045] S12: Mix anhydrous ethanol and deionized water at a volume ratio of 1:1 to 1:3 to obtain 300 to 600 mL of ethanol mixture; add 1 to 3 g / L of oxalic acid deionized water dropwise to the obtained ethanol mixture until the pH of the solution is 4.0 to 4.7; then add 0.5 to 2 g of KH570 silane coupling agent to the solution to obtain KH570 aqueous solution; place the obtained KH570 aqueous solution in an environment of 20 to 26 °C for hydrolysis for 0.5 to 1 hour.

[0046] S13: Add the dried silica fume obtained in step S11 to the KH570 aqueous solution after hydrolysis in S12, and ultrasonically disperse for 5-10 minutes to obtain a silica fume dispersion.

[0047] S14: Stir the silica fume dispersion obtained in S13 at 60-70°C using a magnetic stirrer for 0.5-1.5 hours.

[0048] S15: Centrifuge the silica fume dispersion obtained in S14 and repeatedly wash away the residual KH570 in the solution with an aqueous ethanol solution to obtain silica fume filter material.

[0049] S16: Dry the silica fume filter material obtained in S15 at 60-80℃ for 10-12 hours to obtain modified silica fume.

[0050] As a preferred embodiment of the present invention, the initial flowability of the slurry for preparing the modified silica fume porous lightweight concrete-based thermal insulation material should be 125-138 mm, and the initial yield stress should be 22.0-32.5 Pa.

[0051] This invention also provides a method for preparing the above-mentioned modified silica fume porous lightweight concrete-based thermal insulation material, such as... Figure 2 As shown, the specific preparation steps are as follows:

[0052] S21: Weigh all raw materials, add cement, ultrafine filler, modified silica fume, lime, early strength agent and foam stabilizer into the mixing pot, and stir at medium speed (600-900 rpm) for 0.5-1 minutes to obtain the first mixture.

[0053] During stirring, the water-reducing agent is mixed evenly with a portion of the water to obtain a water-reducing agent solution. The remaining water is then mixed evenly with the gas-generating agent, and stirred thoroughly with a glass rod to obtain a gas-generating agent solution.

[0054] S22: After the stirring in S21 is completed, the obtained water-reducing agent solution is added to the first mixture in the mixing pot and stirred at high speed (2000-2300 rpm) for 3-5 minutes. Then, the obtained gas-generating agent solution is added to the mixing pot and stirred at high speed for 0.5-1 minutes to obtain a slurry.

[0055] S23: After S22 is finished, quickly pour the slurry obtained from S22 into the mold, shake it slightly to mix it evenly, and place it in a curing chamber at 24-29℃ and 60%-90%RH for static gas generation for 1-2 days.

[0056] S24: After the gas generation is completed, demold and continue curing in a curing chamber at 24-29℃ and 60%-90%RH for 3-7 days.

[0057] S25: After curing, place it in a forced-air drying oven at 100-110℃ to dry to constant weight, and then place it in a drying tank to cool, finally obtaining the modified silica fume porous lightweight concrete-based thermal insulation material of the present invention.

[0058] Example

[0059] This embodiment prepares a modified silica fume porous lightweight concrete-based thermal insulation material, as detailed below:

[0060] The modified silica fume was first prepared, and the specific process is as follows:

[0061] S1: Weigh 20g of ordinary silica fume with an average particle size of 0.13μm and dry it at 105℃ for 12 hours.

[0062] S2: Mix anhydrous ethanol and deionized water at a volume ratio of 1:3 to obtain 400 mL of ethanol mixture. Add 3 g / L deionized oxalic acid aqueous solution dropwise to the ethanol mixture until the pH of the solution reaches 4.5. Then add 0.85 g of KH570 silane coupling agent to obtain KH570 aqueous solution. Place the KH570 aqueous solution in an environment of 26 °C for 1 hour for hydrolysis.

[0063] S3: Add 20g of dry ordinary silica fume to the hydrolyzed KH570 aqueous solution and ultrasonically disperse for 10 minutes to obtain silica fume dispersion.

[0064] S4: Stir the silica fume dispersion at 70°C for 1 hour using a magnetic stirrer.

[0065] S5: Centrifuge the silica fume dispersion and repeatedly wash away residual KH570 with an aqueous ethanol solution to obtain silica fume filter material.

[0066] S6: The silica fume filter material is dried at 60°C for 12 hours to obtain modified silica fume.

[0067] The average particle size of the modified silica fume was measured to be 0.10 μm, and the average contact angle was 69.9°.

[0068] Subsequently, based on the obtained modified silica fume, a modified silica fume porous lightweight concrete-based thermal insulation material was prepared. The specific process is as follows:

[0069] S1: Weigh out 97.5g of ordinary silicate cement, 137.5g of fly ash, 10g of modified silica fume, 5g of lime, 3.9g of calcium chloride, 1.25g of calcium stearate, 1.25g of aluminum powder paste, 3g of water-reducing agent and 120g of water in sequence.

[0070] S2: Add all raw materials except for the foaming agent, water-reducing agent, and water to the mixing bowl and stir at 600 rpm for 1 minute. During stirring, mix the water-reducing agent with some water evenly to obtain a water-reducing agent solution. Then mix the remaining water with the foaming agent evenly and stir thoroughly with a glass rod to obtain a foaming agent solution.

[0071] S3: After stirring in S2, the water-reducing agent solution was added to the mixing pot and stirred at 2000 rpm for 3 minutes. Then, the gas-generating agent solution was added to the mixing pot and stirring at high speed was continued for 1 minute to obtain a slurry. The initial fluidity and yield stress of the slurry were measured to be 132.46 mm and 26.5 Pa, respectively.

[0072] S4: After S3 mixing is completed, quickly pour the slurry into the mold, shake it gently to mix evenly, and place it in a curing chamber at 25℃ and 90%RH for 1 day to allow it to stand and generate gas.

[0073] S4: After the gas generation is complete, demold and continue curing in a curing chamber at 25℃ and 90%RH for 3 days.

[0074] S5: After curing, place it in a 105℃ forced-air drying oven to dry to constant weight, and then place it in a drying tank to cool to obtain the modified silica fume porous lightweight concrete-based thermal insulation material of the present invention (i.e., a modified porous concrete).

[0075] Comparative Example

[0076] This comparative example yielded a common porous concrete, and the specific method is as follows:

[0077] S1: Weigh out 97.5g of ordinary Portland cement, 147.5g of fly ash, 5g of lime, 3.9g of calcium chloride, 1.25g of calcium stearate, 1.25g of aluminum powder paste, 1.7g of water-reducing agent and 120g of water in sequence.

[0078] S2: Add all raw materials except for the foaming agent, water-reducing agent, and water to the mixing bowl and stir at 600 rpm for 1 minute. During stirring, mix the water-reducing agent with some water evenly to obtain a water-reducing agent solution. Then mix the remaining water with the foaming agent evenly and stir thoroughly with a glass rod to obtain a foaming agent solution.

[0079] S3: After stirring in S2, the water-reducing agent solution was added to the mixing pot and stirred at 2000 rpm for 3 minutes. Then, the gas-generating agent solution was added to the mixing pot and stirring at high speed was continued for 1 minute to obtain a slurry. The initial fluidity and yield stress of the slurry were measured to be 133.76 mm and 26.1 Pa, respectively.

[0080] S4: After S3 mixing is completed, quickly pour the slurry into the mold, shake it gently to mix evenly, and place it in a curing chamber at 25℃ and 90%RH for 1 day to allow it to stand and generate gas.

[0081] S4: After the gas generation is complete, demold and continue curing in a curing chamber at 25℃ and 90%RH for 3 days.

[0082] S5: After curing, place it in a 105℃ forced-air drying oven to dry to constant weight, and then place it in a drying tank to cool to obtain ordinary porous concrete.

[0083] The materials obtained in the examples and comparative examples were characterized and verified as follows:

[0084] To investigate the changes in physical properties before and after silica fume modification, Fourier transform infrared spectroscopy was first performed to characterize the changes in its surface functional groups, such as... Figure 3 As shown. Next, TEM testing was performed to analyze the dispersion of silica fume before and after modification, as shown. Figure 4 As shown. Finally, the foam stabilization effect before and after silica fume modification was tested, as shown. Figure 5 As shown. In addition, photographs of the pore structures of ordinary porous concrete and modified silica fume porous lightweight concrete-based insulation materials were taken, as shown. Figure 6 As shown in Table 1, the apparent density, compressive strength, and thermal conductivity at 20℃ of ordinary porous concrete and modified silica fume porous lightweight concrete-based thermal insulation materials were measured.

[0085] The results are as follows:

[0086] Depend on Figure 3 It can be seen that the functional groups on the surface of silica fume changed significantly after modification with KH570: at 1697 cm⁻¹ -1 The C=O stretching vibration peak was enhanced at 1054 cm⁻¹. Meanwhile, at 1054 cm⁻¹... -1 The antisymmetric stretching vibration peak of Si-O-Si at 800 cm⁻¹ -1 474cm -1 The absorption peaks of both the Si-O-Si symmetric stretching and bending vibrations were significantly enhanced, while those at 3400 cm⁻¹ were significantly enhanced. -1 The -OH peak at the point was significantly weakened. These findings indicate that KH570 was successfully coupled to the silica fume surface, reducing the number of alcohol groups on the silica fume surface and replacing them with hydrophobic functional groups, thereby increasing the contact angle of the modified silica fume.

[0087] Depend on Figure 4 It can be seen that KH570 modification not only increases the contact angle of silica fume, but also improves the dispersion effect of silica fume. Ordinary silica fume, due to its low hydrophilicity, exhibits significant agglomeration in solution. However, after modification with KH570, the steric hindrance effect and electrostatic repulsion of surface functional groups hinder the agglomeration between silica fume particles, resulting in a reduction in average particle size.

[0088] like Figure 5 and Figure 6 As shown, within the particle size and contact angle range specified in this invention, silica fume with a larger particle size can still be stably adsorbed to the gas-liquid interface and exhibit excellent bubble stabilization effect, showing a decrease in average pore size, a more concentrated pore size distribution, a more rounded pore shape, and a decrease in the proportion of interconnected pores.

[0089] For porous materials, the pore structure plays a dominant role in their thermal insulation performance. With the addition of modified silica fume, the pore structure of porous concrete is significantly optimized, thereby reducing the material's thermal conductivity at room temperature. Simultaneously, thanks to the high reactivity of silica fume, the 3-day compressive strength of the modified silica fume porous lightweight concrete-based insulation material is increased from 0.41 MPa to 0.51 MPa, demonstrating a remarkable improvement.

[0090] Table 1 Comparison of physical properties of ordinary / modified silica fume porous lightweight concrete-based thermal insulation materials

[0091]

[0092] This invention modifies silica fume of a specific particle size, controlling its contact angle within an optimal range. This modified silica fume can then be stably adsorbed at the gas-liquid interface, significantly improving the foam stabilization effect of the slurry and thus optimizing the pore structure and insulation performance of the porous lightweight concrete-based insulation material. The modified silica fume porous lightweight concrete-based insulation material proposed in this invention has the advantages of being lightweight, possessing excellent thermal insulation and sound insulation effects, good strength performance, and low cost, making it suitable for various insulation applications.

[0093] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the invention. Therefore, all technical solutions obtained through equivalent substitution or transformation fall within the protection scope of the present invention.

Claims

1. A modified silica fume porous lightweight concrete-based thermal insulation material, characterized in that, The slurry composition of the modified silica fume porous lightweight concrete-based thermal insulation material per 100 parts by weight includes: 25.0~27.2 parts of cement, 36.0~37.1 parts of ultrafine filler, 0.9~3.1 parts of modified silica fume, 0.6~1.6 parts of lime, 0.7~1.2 parts of early strength agent, 0.2~0.4 parts of foam stabilizer, 0.2~0.4 parts of gas generating agent, 0.4~0.9 parts of water reducing agent, and 31.3~32.6 parts of water; The modified silica fume has a particle size of 0.01~12 μm, an average particle size of not less than 0.1 μm, and a contact angle of 65~83°. The initial fluidity of the slurry is 125~138 mm, and the initial yield stress is 22.0~32.5 Pa; The gas-generating agent is a surfactant, hydrogen peroxide, or aluminum powder paste; The specific method for preparing the modified silica fume is as follows: S11: Weigh 10~30 g of silica fume and dry it at 105 ℃ for 8~15 hours to obtain dried silica fume; S12: Mix anhydrous ethanol and water in a volume ratio of 1:1 to 1:3 to obtain 300 to 600 mL of ethanol mixture; add oxalic acid aqueous solution with a concentration of 1 to 3 g / L dropwise to the ethanol mixture until the pH of the solution is 4.0 to 4.7; then add 0.5 to 2 g of KH570 silane coupling agent to obtain KH570 aqueous solution; place the KH570 aqueous solution in an environment of 20 to 26 °C for hydrolysis for 0.5 to 1 hour; S13: Add the dried silica fume to the hydrolyzed KH570 aqueous solution and ultrasonically disperse for 5-10 minutes to obtain a silica fume dispersion; S14: Stir the silica fume dispersion at 60~70 ℃ for 0.5~1.5 hours; S15: Centrifuge the silica fume dispersion obtained in S14 and repeatedly wash away the residual KH570 in the solution with ethanol aqueous solution to obtain silica fume filter material; S16: Dry the silica fume filter material at 60~80 ℃ for 10~12 hours to obtain modified silica fume.

2. The modified silica fume porous lightweight concrete-based thermal insulation material according to claim 1, characterized in that, The cement is silicate cement or early-strength sulfoaluminate cement, and the ultrafine filler is fly ash or metakaolin.

3. The modified silica fume porous lightweight concrete-based thermal insulation material according to claim 1, characterized in that, The early strength agent is a calcium chloride type early strength agent or a sodium sulfate type early strength agent, the foam stabilizer is a calcium stearate type foam stabilizer, and the water reducing agent is a polycarboxylate type water reducing agent.

4. A method for preparing a modified silica fume porous lightweight concrete-based thermal insulation material according to any one of claims 1 to 3, characterized in that, Specifically as follows: S21: Cement, ultrafine filler, modified silica fume, lime, early strength agent and foam stabilizer are stirred at 600~900 rpm for 0.5~1 minutes to obtain the first mixture; water-reducing agent is uniformly mixed with some water to obtain water-reducing agent solution; the remaining water is uniformly mixed with gas-generating agent to obtain gas-generating agent solution. S22: Add the water-reducing agent solution to the first mixture and stir at 2000~2300 rpm for 3~5 minutes, then add the gas-generating agent solution and continue stirring for 0.5~1 minutes to obtain a slurry; S23: Pour the slurry into the mold, shake it evenly, and then place it under static conditions of 24~29℃ and 60%~90%RH for 1~2 days to allow it to generate gas. S24: Demold after the gas generation is complete, and continue to cure at 24~29 ℃ and 60%~90%RH for 3~7 days; S25: After curing, dry at 100~110 ℃ to constant weight, and after cooling, obtain the modified silica fume porous lightweight concrete-based thermal insulation material.

Citation Information

Patent Citations

  • Light high-strength anti-crack cement-based building heat insulating material and preparation method thereof

    CN109081653A

  • Lightweight foam concrete

    CN117964305A